Environmental health assessment of communities across Canada: contextual factors study of the Canadian Alliance for Healthy Hearts and Minds. Issue 2 (30th November 2018) - de Souza, R. J.; Gauvin, L.; Williams, N. C.; Lear, S. A.; Oliveira, A. P.; Desai, D.; Corsi, D. J.; Subramanian, S. V.; Rana, A.; Arora, R.; Booth, G. L.; Razak, F.; et al.
ABSTRACT: Rationale : Cardiovascular risk varies across communities in Canada. Community-level differences in contextual factors may influence risk factor development. Methods : We audited urban and rural Canadian communities using a standardized instrument to collect objective measures of demographic, public transport, tobacco, grocery, alcohol, and healthful restaurant options. We duplicated 209 audits to assess reliability. Results : Of 2074 communities audited between 2014 and 2016, 83.5% were urban. Provincial and urban-rural differences exist in fruit and vegetable availability. Rural communities face higher food prices, are subject to more seasonal variation in fruit and vegetable selection, and generally see less promotion of healthy choices and nutritional information in restaurants than urban communities. In-store advertising for sweet drinks and junk food is more frequent than advertisements for tobacco products. Cigarette prices are lower and variety higher in urban than rural communities, and lowest in central Canada. Alcohol prices are lowest in Quebec. The intra-rater reliability of the audits was high. We created an on-line map for public use. Conclusions : Provincial and urban-rural differences exist for contextual determinants of health. Public health and built environment professionals and government officials should use these data to develop unified federal and provincial strategies to reduce Canada's chronic disease burden.